Mencegah Penularan Covid-19 Di Bandar Udara Melalui Instrumen Hukum - M Hadyan Yunhas Purba; Hasim Purba; Aflah; Siti Nurahmi Nasution (Jurnal Ilmiah Penegakan Hukum, 2022)
This article aims to examine the implementation of the Regulation of the Minister of Transportation No.18 of 2020 concerning Transportation Control in the Context of Prevention of Covid-19 (“MoTR No.18/2020”) as amended by Regulation of the Minister of Transportation No.41 of 2020 which serves as a guideline for infrastructure providers. transportation such as managers of terminals, stations, seaports and airports in implementing health protocols and transportation control. This research combines normative juridical law research methods and empirical legal research. Normative legal research is carried out by taking an inventory of related laws and regulations, journals, other encyclopedias related to the topic of this research. Meanwhile, empirical legal research was conducted by conducting interviews with the management of PT. Angkasa Pura II (Persero) Kuala Namu and direct observation at Kuala Namu Airport. The data obtained will then be analyzed qualitatively and deductive conclusions are drawn. The results obtained, that there are still some discrepancies in the application of health protocols properly and correctly due to lack of awareness to carry out health protocols and the absence of strict sanctions and supervision for violations of these